A condição de trabalho dos professores na região oeste do Paraná, na perspectiva dos docentes que atuam nocurso de formação de docentes integrado, em nível médio - Almeida, Marcia Aparecida Silita de (2014)
This research has to goal the study the working conditions of teachers working in the training course for teachers Secondary Level in the western region of Paraná in 2012. Takes into account changes in education policy from the 1990s and its influence on the organization and offer of professional education. It presents a literature review about the characteristics of teaching, the history of professional education in Brazil and about the educational policies of the 1990s and its influence on professional education in the state of Paraná, in particular concerning the course of teacher - Secondary Level. Emphasizes the creation of PROEM suggested that the closing of the offering professional courses in public schools since 1997, the almost total closure of such courses and their subsequent recovery. It also presents an empirical survey on the subject of this study, results of a questionnaire to teachers from schools in four cities of western Paraná. From the collection and tabulation of the data they were compared to other studies carried out in the country and investigating different aspects of education and working conditions of teachers in the country, and the result is an overview of the working conditions of teachers in the region western Parana.